The deterrent effects of Brazilian child labor law - Oliveira, Cristiano Aguiar de; Machado, Gabriel Costeira (Revista de Estudos Empíricos em Direito, 2020)
Brazilian law prohibits all forms of work for children under the age of 14 years old. Therefore, work performed by children under 14 years of age is subject to sanctions that do not apply to work performed by those over 14 years of age. We use this quasi-experiment generated by Brazilian law to test the deterrent effects of such sanctions. For this purpose, we use the 2013 Pesquisa Nacional de Amostra por Domicílios (PNAD) data to estimate the local average treatment effects (LATE) using the regression discontinuity approach. The results indicate that on average, this law results in 88% fewer weekly working hours when individuals living in rural and urban areas are considered. The effects in rural areas are thus inconclusive. The paper concludes that the law has a deterrent effect and reduces child labor in Brazil, but the effects are ambiguous in rural areas, where law enforcement is weaker and more children work.